Analisis Faktor Yang Mempengaruhi Keselamatan Operasional Kapal di Pelabuhan Merak - Cholis Imam Nawawi; Rahmat Santoso; Budi Purnomo (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
The study, titled "Analysis of Factors Affecting Safety at Merak Port," aims to identify and analyze key factors influencing operational safety at Merak Port. This port is a strategic route linking Java and Sumatra, serving millions of passengers and vehicles annually. However, high activity levels and operational complexity present significant safety challenges. This research employs a qualitative case study approach, combining interviews, field observations, and document analysis. Quantitative data were also collected via questionnaires distributed to operators, workers, and passengers. Findings reveal that human factors, weather conditions, and infrastructure are critical to safety. Incidents in 2023, such as the KMP Royce 1 fire and a crane accident, underscore the need for enhanced risk management and infrastructure maintenance. The study concludes that gaps in safety training and compliance with safety procedures are key challenges. Additionally, extreme weather and suboptimal heavy equipment conditions increase operational risks. Recommendations include improving safety management practices, enhancing infrastructure maintenance, and providing regular training for workers to strengthen operational safety at Merak Port.